Evaluation of mechanical and ballistic properties of abaca–polyester composites as a candidate material for bulletproof vests - Arif, Zainal; Adlie, Taufan Arif; Yakob, Iskandar; Widodo, Syamsul Bahri; Suheri, Suheri; Ritonga, Abriandi Sahputera; Sariyusda, Sariyusda (Politeknik Negeri Lhokseumawe, 2025)
This study aims to analyze the mechanical and ballistic properties of abaca (Musa textilis) fiber–reinforced polyester (BQTN 157) composites as an alternative candidate material for bulletproof vest panels. Variations in fiber orientation (bias-woven fiber, straight-woven fiber, and straight fiber) and fiber mass fractions (10%, 20%, and 30%) were applied to evaluate their influence on tensile strength, impact toughness, and ballistic response. The tensile test results revealed that the straight fiber alignment at a 10% mass fraction exhibited the best tensile strength of 54.12 MPa, strain of 0.021 mm/mm, the toughness of 43.90 kJ/m2, and an elastic modulus of 2577 MPa. In the impact test, the same configuration achieved the maximum absorbed energy of 2.70 J. The ballistic testing with 9 mm FMJ projectiles (NIJ Level IIIA) demonstrated that all specimens with thicknesses of 15 mm and 20 mm experienced full penetration. The dominant failure mechanisms included delamination, fiber pull-out, matrix fracture, and shear plugging. These findings indicate that although abaca fiber composites possess good mechanical performance and sustainability advantages, further material engineering strategies—such as hybridization with synthetic fibers or the addition of ceramic/metallic layers—are required to enhance their ballistic resistance. Abaca–polyester composites require hybridization with synthetic fibers or additional protective layers to be viable for ballistic applications.